AVALIAÇÃO DE SISTEMAS PREDIAIS EM EMPREENDIMENTOS HABITACIONAIS DO SEGMENTO ECONÔMICO POR MEIO DA APO - Teles, Andreia Regina Montresol; Ono, Rosaria (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Housing life cycle should be understood not only by its stages of conception, design or execution per se, but also from its conclusion. In other words, by its operation. Studies done during the growing of the Real State market in Brazil, intensified by the "Growth Acceleration Program) - PAC (2007)", also known as" My House, My Life", concluded that the quality of the national housing production underperformed the expectations. In turn, with the adoption of ABNT NBR 15.575/2013, supported by the new civil code and consumer rights, has ing their rights, as provided to any other consumer goods. This paper intends to provide a deeper exploration about a performance evaluation method applied to building systems in housing constructions, by using techniques of Post-Occupancy Evaluation (POE) in apartment buildings for real state market located at the Sao Paulo metropolitan region. The goal is to present the survey output from residents and an analysis about the hydro-sanitary system performance, mentioned as a growing trendy topic by academic Researchers.